Superconvergence Analysis of Finite Element Method for a Second-Type Variational Inequality - Dongyang Shi; Hongbo Guan; Xiaofei Guan (Journal of Applied Mathematics)
This paper studies the finite element (FE) approximation to a second-type variational inequality. The supe rclose and superconvergence results are obtained for conforming bilinear FE and nonconforming EQrot FE schemes under a reasonable regularity of the exact solution u∈H5/2(Ω), which seem to be never discovered in the previous literature. The optimal L2-norm error estimate is also derived for EQrot FE. At last, some numerical results are provided to verify the theoretical analysis.